Pharmacokinetics of Raltegravir in the Semen of HIV-Infectedmen. Issue 6 (August 2014) - Antoniou, Tony; Loutfy, Mona R; Brunetta, Jason; Smith, Graham; Halpenny, Roberta; la Porte, Charles
Background: We sought to determine the pharmacokinetic disposition of raltegravir in the blood and seminal plasma of HIV-infected men. Methods: We conducted a pharmacokinetic study using a staggered sampling approach. A total of 16 HIV-infected men receiving raltegravir-based therapy were recruited into the study. Each participant provided six blood plasma and six seminal plasma samples for quantification of drug concentrations in both compartments. Blood and semen samples were obtained within 1 h of each other and were collected prior to the morning dose and at 1, 2, 4, 8 and 12 h post-ingestion. Drug concentrations were determined by liquid chromatography tandem mass spectrometry. Results: A total of 96 semen samples and 96 blood samples were obtained from all participants during the study period. The median age and baseline CD4 + T-cell count of the study participants were 48 years (IQR 42–53) and 450 cells/mm 3 (IQR 289–585). Virological suppression to <50 copies/ml had been maintained for a median of 21 months (IQR 7–35) at the time of study enrolment. The median seminal plasma-to-blood plasma ratios and AUC0–12 h seminal plasma-to-blood plasma ratios of raltegravir were 3.25 (IQR 1.46–5.37) and 2.26 (IQR 1.05– 4.45), respectively. Conclusions: Concentrations of raltegravir in seminal plasma are several fold higher than those attained in blood plasma and those required to inhibit viral replication in this compartment. Further research examining the therapeutic and prophylactic implications of these findings is warranted.